Do joint fighter programs save money? : technical appendixes on methodology - Lorell, Mark A.; Kennedy, Michael; Leonard, Robert S.; Munson, Ken; Abramzon, Shmuel; An, David L.; Guffey, Robert A. (Rand Corporation monograph series ;, 2013)
These appendixes explain the methodology used in an analysis of the costs and savings of joint aircraft acquisition programs. They illustrate calculations for theoretical maximum joint aircraft savings in acquisition and in operations and support, historical joint aircraft cost-growth premiums, savings needed to offset premiums, and two cost-comparison methodologies.